2002
DOI: 10.1074/jbc.m202860200
|View full text |Cite
|
Sign up to set email alerts
|

Protein Farnesyltransferase and Protein Prenylation inPlasmodium falciparum

Abstract: Comparison of the malaria parasite and mammalian protein prenyltransferases and their cellular substrates is important for establishing this enzyme as a target for developing antimalarial agents. Nineteen heptapeptides differing only in their carboxyl-terminal amino acid were tested as alternative substrates of partially purified Plasmodium falciparum protein farnesyltransferase. Only NRSCAIM and NRSCAIQ serve as substrates, with NRSCAIM being the best. Peptidomimetics, FTI-276 and GGTI-287, inhibit the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
122
0
6

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 61 publications
(67 reference statements)
8
122
0
6
Order By: Relevance
“…7,8,12 While inhibition of farnesyltransferase has been demonstrated to have limited toxicity to mammalian cells at concentrations required to elicit a therapeutic response, 8 selective inhibition of parasitic farnesyltransferase may yet be an essential goal in the development of safe and effective antimalarial PFT inhibitors. To examine the selectivity of this new series of PFT inhibitors, 12 compounds were chosen on the basis of structural diversity and in vitro PfPFT activity and their 50% inhibition concentrations (IC 50 ) against both PfPFT and rat PFT were determined (Table 5).…”
Section: Selectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…7,8,12 While inhibition of farnesyltransferase has been demonstrated to have limited toxicity to mammalian cells at concentrations required to elicit a therapeutic response, 8 selective inhibition of parasitic farnesyltransferase may yet be an essential goal in the development of safe and effective antimalarial PFT inhibitors. To examine the selectivity of this new series of PFT inhibitors, 12 compounds were chosen on the basis of structural diversity and in vitro PfPFT activity and their 50% inhibition concentrations (IC 50 ) against both PfPFT and rat PFT were determined (Table 5).…”
Section: Selectivitymentioning
confidence: 99%
“…In an effort to reduce development costs and accelerate access to new antimalarials, recent attention has been directed toward identifying antimalarial activity from agents developed for the treatment of other diseases. [7][8][9][10][11] On recognizing the essential role of prenylation for cellular function in lower eukaryotes, 7,12 several groups have investigated the antimalarial potential of inhibitors of protein farnesyltransferase (PFT a),8,13-16 a recognized key target for the interception of aberrant Ras activity common to many (~30%) human cancers. 17 Nallan et al have recently surveyed a number of mammalian-cell-optimized PFT inhibitors that are in clinical and preclinical development, including those from Bristol-Myers Squibb (BMS) (e.g., 1 16 and 2 8 ) and from the Hamilton/Sebti group (e.g., 3a and 3b ),13 for their abilities to inhibit Plasmodium falciparum PFT (PfPFT a ) enzyme activity (as determined by IC 50 values) and to arrest the in vitro growth of the intraerythrocytic forms of P. falciparum (as determined by ED 50 values, Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…A recent genomic and phylogenic comparison revealed that apicomplexa contain unusual calcium response pathways that need deeper investigations and could be exploited as new therapeutic agents (Nagamune & Sibley, 2006 (Gelb et al, 2003). Furthermore, interest was strengthened by the fact that peptidomimetics and prenyl analogues of PFT substrates were shown to inhibit in vitro parasite growth (Chakrabarti et al, 2002;Ohkanda et al, 2001). Although the PGGT-I activity was reported, searches in the P. falciparum genome database revealed an apparent absence of PGGT-I gene .…”
Section: Sarcoplasmic/endoplasmic Reticulum Calcium Pfatpase (Serca)mentioning
confidence: 99%
“…These are consistent with the CaaX specificity of the T. cruzi PGGT-I (Table1). Alterations in the residues involving substrate interactions in PFT and PGGT-I subunits between protozoan and mammalian orthologs may cause substantial differences in binding specificity for the CaaX motif and smallmolecule inhibitors in protozoa and mammalian cells [15][16][17][18][19][20][21]40]. This suggests not only different selectivity of inhibitors against parasite PFT and PGGT-I from that of mammalian enzymes but also differential consequences of inhibitory effects of PGGT-I or PFT on cellular events in the parasites from those in mammalian cells.…”
Section: Inhibitor Studiesmentioning
confidence: 99%
“…PFT has been found in pathogenic protozoan parasites including trypanosmatids (T. cruzi, T. brucei, and Leishmania), the malaria parasite (Plasmodium falciparum), and the enteric parasite Entamoeba histolytica [15][16][17][18]. PGGT-I has recently been found in E. histolytica [19].…”
Section: Introductionmentioning
confidence: 99%